A study of clinical outcome, prevalence and molecular characterization of vancomycin resistant enterococci (VRE) at a tertiary care centre - Laxmi Kant Khanal; R. Sujatha; Anil Kumar; Ambika Bhatiani; Desh Nidhi Singh (Al Ameen Medical College, 2021)
Background: Vancomycin resistant enterococci (VRE) has rapidly become one of the leading cause of nosocomial infections and major growing problems in health care facilities globally. Objectives: To determine prevalence, perform molecular characterization and to see the clinical outcome of VRE at a tertiary care centre. Materials and methods: A total of 122 enterococci isolates collected from various clinical specimens except stool obtained in Clinical Microbiology Laboratory of Rama Medical College Hospital and Research Centre, Kanpur were processed for species differentiation. VRE were detected by MIC determination of vancomycin using agar dilution method. Molecular characterisation of VRE was done for detection of VanA and VanB genes by conventional PCR. Clinical outcome of VRE infected cases were analysed by patient medical records. Results: Prevalence of VRE was found to be 6.5% (8/122). (75%) 6/8 were E. faecium and (25%) 2/8 were E. faecalis. By AST report, among VRE, resistance to teicoplanin was 100%, that to penicillin was 100%, norfloxacin 100%, levofloxacin 100%, high level gentamycin (HLG) 100%, high level streptomycin (HLS) 87.5%, erythromycin 87.5%, ciprofloxacin 87.5%, nitrofurantoin 83.3% and that to linezolid was 12.5%. Gene detection by PCR showed 3 VanA and 1 VanB genes out of 8 VRE and among 5 VRE, VanA or VanB genes were not detected. Mortality was seen in one case of VRE, who had mixed infection with Klebsiella pneumoniae and was resistant to linezolid. Conclusion: Prevalence of VRE and high level aminoglycoside resistance among them seems high. Prudent use of vancomycin, strict enforcement of infection control policies in hospital and surveillance detection of VRE in hospital should be done regularly.